Code-Switching in Classroom Teaching - Mahato, Rajendra Prasad (Academic Voices: A Multidisciplinary Journal, 2018)
Code-switching refers to the way of communication that bridges two or more linguistic variet ies to resister in a single conversat ion. Especially, in secondary level class-room teachings in English medium schools, ode-switching, for this particular research, has been analyzed and interpreted to conclude that among innumerable reasons deliberately or unknowingly the environment of the classroom mainly feels the echo of code-switching to facilitate understanding for the students. Code-switching, however, is the need of the teachers. Academic Voices Vol.6 2016: 28-31